Deep Learning and the Love-Based Curriculum in Madrasah Ibtidaiyah: Implications for the Implementation of the Merdeka Curriculum - Mohamad Azhar Annawa UBM; Dewi Susilo Reni; Wulan Feronika Maharani (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2026)
The emergence of the Deep Learning approach and the Love-Based Curriculum (Kurikulum Berbasis Cinta/KBC) amid the implementation of the Merdeka Curriculum has raised fundamental questions among madrasah educators regarding whether these approaches function as replacements for, or complements to, the existing curriculum. This study aims to examine the conceptual role and interrelationship among Deep Learning, the Love-Based Curriculum, and the Merdeka Curriculum in the context of Madrasah Ibtidaiyah education. The study employs a qualitative library research method through a systematic review of literature retrieved from the Google Scholar database, including national and international journal articles and relevant educational policy documents published between 2021 and 2026. The findings indicate that Deep Learning and the Love-Based Curriculum are not substitutes for the Merdeka Curriculum; rather, the three form a synergistic layered curriculum model. The Merdeka Curriculum functions as the national policy foundation that determines educational direction and learning outcomes, Deep Learning serves as an operational pedagogical approach that promotes reflective, meaningful, and engaging learning processes, while the Love-Based Curriculum functions as a value framework and distinctive ethos of madrasah education that cultivates the concept of Panca Cinta, encompassing spiritual, intellectual, social, ecological, and national dimensions. These findings suggest that teachers in Madrasah Ibtidaiyah should integrate all three approaches into a holistic learning ecosystem rather than treating them as separate or alternative options.